Антиоксидантна активність полімерного біоциду полігексаметиленгуанідин гідрохлориду - Kamenieva, Т.М.; Tarasyuk, O.P.; Derevianko, K.Yu.; Aksenovska, O.A.; Shybyryn, O.V.; Metelytsia, L.O.; Rogalsky, S.P. (V.P. Kukhar Institute of Bioorganic Chemistry and Petrochemistry of the National Academy of Sciences of Ukraine, 2020)
Cationic polymer polyhexamethylene guanidine hydrochloride (PHMG-Cl) is promising biocide that combines a broad spectrum of antimicrobial activity, moderate toxicity, as well as reasonable cost. It is widely used as an effective disinfectant in cooling systems, swimming pools, and hospitals, personal hygiene products, etc. Recently PHMG-Cl was found to have pronounced anti-inflammatory and wound healing properties and therefore may be used for the treatment of chronic wounds and thermal burns. This may indicate the antioxidant activity of polymeric biocide. In this study, PHMG-Cl has been synthesized by melt polycondensation of guanidine hydrochloride and 1,6-hexamethylenediamine. The structure of the cationic polymer was confirmed by 1H NMR and IR spectroscopy. The viscosity-average molecular weight of PHMG-Cl was found to be 10700. The antioxidant activity of PHMG-Cl has been studied by using different methods. In the methylene blue (MB) dye test, the oxidation of MB by hydroxyl radicals generating in Fenton’s system was found to decrease in the presence of PHMG-Cl in a molar ratio to MB of 5:1 and 10:1 (by 26 % and 38 %, respectively). At the same time, complete dye oxidation was observed when guanidine hydrochloride was used instead of PHMG-Cl. The antioxidant activity of PHMG-Cl has also been studied in the model system of radical chain oxidation of benzyl alcohol (BA). In this system, alkyl and peroxyl radicals are formed. The antioxidant activity was determined by a decrease of the initial rate of oxygen absorption during the initiated oxidation of BA. The introduction of PHMG-Cl into the oxidized system in the concentrations ranged from 1.3·10-3 - 1.6·10-2 mol/l decreased the oxidation rate of BA by 4.5–88 %. This result demonstrates that PHMG-Cl effectively inhibits radical chain oxidation of BA. However, further research is needed to elucidate the mechanism of free radical deactivation by a polymer biocide.